(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Oral surgical procedures gives rise to aerosols which include saliva, nasopharyngeal secretion, organic particles and blood.The aerosols act as a carrier for various bacteria and hence become a potent source for infection. Oral surgical procedures are highlyprone to create contamination of aerosols and pathogens which arise from the blood. White coats worn by dentists and the dental chairare highly potent to be contaminated with bacteria and has been an important risk factor in the transmission of infection in the hospital.There is very little evidence available in the current literature regarding contamination of white coats worn by dentists and contaminationpresent in the dental chair. With this background this study was designed to determine the level and type of bacterial contamination onthe white coat and the dental chair in the department of oral and maxillofacial surgery at Karpaga Vinayaga Institute of Dental Sciences,Madhuranthagam, Chengalpet.Materials and method: All the participants were subjected to pre-tested self-administered questionnaire to assess their perception oncontamination of white coat and the frequency of washing. Samples for the study were taken from the white coats of undergraduatefinal year students, interns and various sites of dental chair. Sampling was carried out by an inert vector and the microorganisms wererecovered later for analysis. Sterile cotton swab, and Stuart’s transport media with proper microbiological quality control check whichwere Approved by Clinical Laboratory Standards Institute were used.Result: Among 200 students, participants more than half of the students (60%) stated that the number of white coats used in a weekwas one, of which 75% were final year students and 45% were interns. It was found to be statistically significant (P=0.032*). Majorityof the final year students (70%) reported that their white coat was last washed a week ago and there was a statistically significantdifference found between final year and interns (P = 0.021*). Almost 50% of interns got their white coats washed twice a week and70% of final years once a week. There was a statistically significant difference found between final year and interns (P = 0.024. Morethan half (55%) of the study participants wear their white coats before entering the respective department or laboratory, of which (87%)were final years and (23%) were interns and it was found to be statistically significant (P=0.036*). Interestingly, a greater number ofstudents (90%) agreed that they never had the practice of exchanging their white coat with their colleagues some or the other time, ofwhich 88% were final years and 92% were interns.Conclusion: White coats have been shown to harbor potential contaminants and may have a role in cross infection of pathogenicmicroorganisms. Thus current study highlight’s the situation of dental cross infection in the form of Students perception, attitude andpractice of having more than one white coat, periodic washing of white coats.